Factors Affecting Mathematics Achievement Among Rural Students: A Scoping Review (2000–2025) - Noel Jimbai Balang (Universitas Muhammadiyah Mataram, 2026)
The disparity in mathematics achievement between rural and urban students remains a global challenge affecting educational equity. Low mathematics achievement among rural students is shaped by interconnected and systemic factors rather than isolated causes. This study aims to map and synthesize key factors influencing rural students’ mathematics achievement based on international literature published between 2000 and 2025. A scoping review methodology following the Arksey and O’Malley framework was employed through systematic searches of ERIC, Scopus, Web of Science, and Google Scholar databases. Data were analyzed using descriptive and thematic approaches. The findings indicate that rural mathematics underachievement is associated with weak foundational skills, language barriers, teacher-centered instructional practices, limited family support, restricted access to technology, uneven teaching quality, and non-diagnostic assessment practices. These interrelated factors contribute to the persistence of the rural–urban achievement gap. The study highlights the need for holistic, context-sensitive, and sustainable interventions to improve mathematics education outcomes in rural settings.